Bioabsorbable stents: nothing from something. (December 2012) - Rajendra, NS; Wrigley, BJ; Gershlick, AH
Percutaneous coronary intervention continues to develop at a rapid pace and has seen exciting developments in the last three decades. Percutaneous coronary intervention numbers have exceeded coronary bypass surgery worldwide and we now have long-term safety and efficacy data on the stents currently being used. However, there are unresolved issues relating to the optimal length of dual antiplatelet therapy, which represent a major concern due to the small but potentially catastrophic effect of stent thrombosis. The latest development in stent iteration is bioabsorbable stent technology. Bioabsorbable technology is still in its infancy; however, it holds promise for the future. This article delineates the progress made so far in this field and ponders its future applications.